2021
DOI: 10.3389/fpls.2021.683228
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Endogenous Melatonin in Resistance to Botrytis cinerea Infection in an Arabidopsis Model

Abstract: Melatonin is an important bioactive molecule in plants. Two synthetases, N-acetylserotonin methyltransferase (ASMT) and serotonin N-acetyltransferase (SNAT) are involved in the final two steps of melatonin synthesis. Melatonin participates in responses to a variety of biotic and abiotic stresses in plants, but few studies have addressed the roles of endogenous melatonin in pathogen resistance. We investigated the role of endogenous melatonin in resistance to Botrytis cinerea infection in an Arabidopsis thalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Among the enzymatic antioxidant defence systems, SOD dismutases O 2 − to O 2 and H 2 O 2 , whereas CAT and POD can convert H 2 O 2 to H 2 O and O 2 in cells [ 55 , 56 ]. Studies had shown that the upregulation of SOD, CAT, and POD activity in the ROS-scavenging system was observed when the resistance response of plants to biotic or abiotic stress occurred [ 47 , 57 , 58 ]. MT treatment can maintain a high scavenging capacity of ROS in cells, which was beneficial to alleviate the extent of membrane lipid peroxidation and preserve the cell membrane integrity [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the enzymatic antioxidant defence systems, SOD dismutases O 2 − to O 2 and H 2 O 2 , whereas CAT and POD can convert H 2 O 2 to H 2 O and O 2 in cells [ 55 , 56 ]. Studies had shown that the upregulation of SOD, CAT, and POD activity in the ROS-scavenging system was observed when the resistance response of plants to biotic or abiotic stress occurred [ 47 , 57 , 58 ]. MT treatment can maintain a high scavenging capacity of ROS in cells, which was beneficial to alleviate the extent of membrane lipid peroxidation and preserve the cell membrane integrity [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its homologous gene in Arabidopsis (AT4G35160, or acetyl serotonin methyltransferase ASMT1 , Berardini et al, 2015 ) has been reported to be expressed in the epidermal L1 layer in the shoot apex. The melatonin biosynthesis pathway was recently shown to be associated with both abiotic ( Wang et al, 2021 ) and biotic ( Zhu et al, 2021 ) stress responses ( Bhowal et al, 2021 ). Members of the melatonin pathway have been shown to be involved in responses to osmotic, drought, and heat stresses ( Bhowal et al, 2021 ), and many of these genes are regulated through miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The role of endogenous melatonin in biotic stress resistance has been investigated in previous studies. A. thaliana that overexpressed ASMT or SNAT showed upregulation of resistance gene expression ( PR1 and PR5 ), increased jasmonic acid (JA) content, smaller lesion size in leaves, and reduced plant disease symptoms [ 90 ].…”
Section: Potential Applications Of Melatonin For the Horticulture Ind...mentioning
confidence: 99%